2021
DOI: 10.1111/joca.12407
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the relationship between risk perceptions and willingness‐to‐pay for commodities during the COVID‐19 pandemic

Abstract: The novel coronavirus disease of 2019 (COVID-19) has had a significant impact on the global retail market. Nonetheless, consumers will eventually return to the market once the pandemic is effectively controlled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…By conducting a multigroup analysis, we find that the relation between anxiety and compulsive buying can be enhanced by utilitarian products, while the relation between fear appeal and compulsive buying is strengthened by hedonic products. The special outcomes of the moderating effect of utilitarian products stem from life-saving purchase decisions and are consumed for the problem-solving purpose (O. Li & Qian, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By conducting a multigroup analysis, we find that the relation between anxiety and compulsive buying can be enhanced by utilitarian products, while the relation between fear appeal and compulsive buying is strengthened by hedonic products. The special outcomes of the moderating effect of utilitarian products stem from life-saving purchase decisions and are consumed for the problem-solving purpose (O. Li & Qian, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The special outcomes of the moderating effect of utilitarian products stem from life-saving purchase decisions and are consumed for the problem-solving purpose (O. Li & Qian, 2022). It is worth noting that the relationship between loneliness and compulsive buying is not significant for different product types.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, results of studies investigating how awe affects consumers’ decisions on food choices revealed that consumer preferences for healthy versus unhealthy products improve with the experience of awe (Cao et al , 2020). At a cognitive-conceptual level, awe differs from other emotions, is characterized by cognitive accommodation and elicited only by information-rich stimuli (Cao et al , 2020) and buffers individuals against losing their possessions (Koh et al , 2019), the effect of risk events on awe is driven by risk perceptions (Li and Qian, 2022) compared with neutral emotion, increases consumers’ likelihood to choose healthy products over unhealthy products because the observed awe effect is driven by consumer processing styles, which increase reliance on analytical processing, thus, leading consumers to prefer healthy products. Consumers with a chronic intuitive rather than analytical processing style are more likely to be influenced by experiences of awe (Cao et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast, research that focused more on generalized or positive influences of the pandemic examined such topics as specific types of consumption behaviors and corresponding changes during the pandemic, including online physical activity behaviors (Cronshaw, 2022 ), food and beverage consumption (Jaud & Lunardo, 2022 ), and effects on sustainable consumption (Hüttel & Balderjahn, 2022 ). Other papers focused more on consumers' psychological responses to the pandemic including risk perceptions and consumer purchase behavior (Li & Qian, 2022 ) and goal orientation effects on well‐being (Sonmez, 2022 ). Articles in this special issue also examined morality based consumer responses including religion versus escape behaviors on life satisfaction (Ekici & Watson, 2022 ), religiosity's influence on service failure response and emotional well‐being (Sarofim et al, 2022 ), and mortality salience and altruism (Jin & Ryu, 2022 ).…”
Section: Introductionmentioning
confidence: 99%